The impact of theory-based educational intervention on improving helmet use behavior among workers of cement factory, Iran - Hamid Jafaralilou; Iraj Zareban; Mohammad Hajaghazadeh; Habibeh Matin; Alireza Didarloo (Journal of the Egyptian Public Health Association, 2019)
Abstract Background The occurrence of occupational accidents is a serious public health issue in industrial workers and may impose life jeopardizing complications. The aim of the study was to assess the effect of a training intervention based on the theory of planned behavior (TPB) on helmet use of workers in cement factories in Khoy and Urmia, Northwest of Iran. Materials and methods This study was a controlled quasi-experimental investigation (before and after) which was conducted on 170 workers employed in Khoy and Urmia cement factories, Northwest of Iran. Eighty-five eligible subjects from Khoy (as intervention group) and 85 similar samples from Urmia (as control group) were selected and recruited. A valid and reliable four-part questionnaire was used to collect the data including socio demographic information, awareness, the theory constructs, and the behavior. After completing the study questionnaire and needs assessment, a specific educational program was implemented on the intervention group only. The effects of education were compared between the groups before and after intervention. The posttest was applied 1 month after educational intervention. Results The mean age of workers in the intervention and control groups was 34.32 ± 8.19 and 33.62 ± 6.17 years, respectively. Before education, the mean score of awareness and helmet use behavior of intervention group was 6.15 ± 3.4 and 5.35 ± 2.8, but after education, those changed into 13.61 ± 3.10 and 9.15 ± 1.65, and the differences were significant (p < 0.01). In addition, before education, the mean score of attitude, subjective norm, behavioral control, and behavioral intention of intervention group was 27 ± 5.17, 37.74 ± 6.92, 29.56 ± 6.17, and 17.65 ± 4.90, respectively. After education, the mean score of those changed into 37.26 ± 4.76, 48.34 ± 5.64, 42 ± 8.07, and 24.79 ± 5.33, respectively, and changes were statistically significant (p < 0.01), while no statistically significant differences were observed in awareness, the behavior, and the theory constructs in the control group after the intervention. Conclusion and recommendations The TPB-based educational approach had a remarkable effect on helmet use of workers. Applying this theory to improve workers’ personal protective behaviors is recommended and emphasized.